2010
DOI: 10.1016/j.breast.2010.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study on the treatment of small breast carcinoma using percutaneous US-guided preferential radiofrequency ablation (PRFA)

Abstract: The purpose of this study was to determine the safety and efficacy of percutaneous ultrasound (US) guided preferential radiofrequency ablation (PRFA) of unifocal human invasive breast carcinoma with largest radiological diameters of up to 16 mm. Thirty-three patients were enrolled in a study to be treated prior to scheduled partial mastectomy. A needle-shaped treatment electrode, successively developed in two different sizes, was placed into the center of the lesions using ultrasound guidance. A temperature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Finally, although precision placement of the electrode is crucial [8] there are currently no means available to facilitate the cumbersome process of manual large diameter electrode placement. Based on initial institutional experience in the use of PRFA in breast cancer patients [2,9] the goal of this study was to move the treatment into an outpatient setting and tackle the identified shortcomings. The radiological protocol for patient selection and treatment follow-up was improved by including MRI and CEUS.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, although precision placement of the electrode is crucial [8] there are currently no means available to facilitate the cumbersome process of manual large diameter electrode placement. Based on initial institutional experience in the use of PRFA in breast cancer patients [2,9] the goal of this study was to move the treatment into an outpatient setting and tackle the identified shortcomings. The radiological protocol for patient selection and treatment follow-up was improved by including MRI and CEUS.…”
Section: Introductionmentioning
confidence: 99%
“…In five studies [21,24,49,59,63], patients withdrew from the study during or after treatment and in another six studies [15,26,44,48,49,72] patients withdrew before the start of the treatment. The overall STROBE score ranged from four to seven (mean…”
Section: Quality Assessmentmentioning
confidence: 99%
“…A total of 63 articles matched the selection criteria. The 63 articles included 16 feasibility studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], 12 phase I studies [29][30][31][32][33][34][35][36][37][38][39][40], nine phase II studies [41][42][43][44][45][46][47][48][49], three comparative studies [50][51][52], one retrospective study [53], and four randomised controlled trials [54][55][56]. In 18 studies the type of study was not reported [8,[57][58][59][60][61][62][63][64]…”
Section: Selected Studiesmentioning
confidence: 99%
See 2 more Smart Citations